Sleep Quality and Associated Factors among Peoples with Epilepsy Who Have a Follow-Up at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia, 2019: An Institutional Based Cross-Sectional Study. (26th July 2020) - Adem, Kemeriya; Kassew, Tilahun; Birhanu, Addis; Abate, Ayalew
Abstract : Background . Sleep is an active cyclic biological phenomenon and necessary for survival. Individuals who suffer from sleep disturbance are less productive, decreased performance, and negative effects on mental health. Despite there are different studies on sleep quality in Ethiopia, no studies have been conducted on magnitude and predictors of sleep quality among people with epilepsy in the study setting. Objective . To assess sleep quality and associated factors among people with epilepsy who have a follow-up at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia, 2019. Method . An institution-based cross-sectional study was employed from May-June 2019. Systematic random sampling following face to face interview technique was employed. Epi-data version 3.1 and SPSS version 25 statistical packages were used for data entry and analysis, respectively. Frequencies, proportions, means, SDs, and cross-tabulations were used to summarize descriptive statistics of the data and tables, texts, and graphs were used for data presentation. To identify association and significant predictor with the outcome variable, binary logistic regression was fitted. The variable which has statistical significance was identified on the basis of p values ≤ 0.05 and AOR with 95% confident intervals. Results . A total of 423 participants have been enrolled to the study with a response rate of 98.1%. The prevalence of poor sleep quality among peoples live with epilepsy was found 65.4% (95% CI: 61.0, 69.9). Being female (AOR = 2.94 ; (95% CI; 1.79, 4.85)), having stress full life events (AOR = 2.38 ; (95% CI; 1.43, 3.97)), nonadherent to AED medication (AOR = 1.86 ; (95% CI; 1.05, 2.78), poly-therapy treatment (AOR = 2.24 ; (95% CI; 1.05, 2.78)), poor seizer control (AOR = 2.4 ; (95% CI; 2.21, 12.46)), comorbid medical illness (AOR = 2.6 ; (95% CI; 1.18, 5.61)), and anxiety (AOR = 2.54 ; (95% CI; 1.52, 4.24)) were factors significantly associated with poor sleep quality. Conclusion . This study revealed that more than half of the study participants were found to have poor sleep quality. So, considering the regular assessment of sleep quality and factors associated followed with appropriate intervention is recommended among peoples living with epilepsy.